Replaceable shoe soles / Ahmad Alif Fahmi, Badrul Wazir and Muhammad Kasyfi - Fahmi, Ahmad Alif; Wazir, Badrul; Rosly, Muhammad Kasyfil Adha (Faculty of Plantation and Agrotechnology, 2023)
Shoe is currently one of the world leading attires in fashion industry with people demanding for them every single day. However, people often buy new shoes due to some factors such as damage, thief incident and many others. The most common factor is due to the weary shoe sole. Every year in the US, people throw away over 300 million pairs of shoes, 95% of which wind up landfills (Tess DiNapoli et. al 2022). The manufacturing process releases large amount of carbon dioxide which is responsible for 1.4% of CHG emissions in the world. A pair of shoes generates 30 pounds of CO2 emissions, keeping a 100-watt light bulb on for a week. The goal of this study is about finding a better substitute material for making shoe soles in order to reduce the large amount of chemical release in shoe manufacturing. One of the reliable products to overcome this problem is the Replaceable Shoe Sole. This replaceable shoe sole can lengthen the life span of your shoes by just replacing a new one and also save the environment without wasting millions of shoes that can cause global harm. This product will also reduce the agricultural waste from coconut industries when using one of their waste product to create the shoe sole.